A critical role of N4-acetylation of cytidine in mRNA by NAT10 in T cell expansion and antiviral immunity - Lu Sun; Xiaoyan Li; Feixiang Xu; Yu‐Wen Chen; Xushuo Li; Zhicheng Yang; Ying Yang; Ke Wang; Tianyi Ren; Zihao Lin; Hua Wang; Xiangdong Wang; et al. (2025)
Following activation, naive T cells exit quiescence and require global translation for rapid expansion, yet the underlying mechanisms remain unclear. Here, we show that during T cell activation, cells upregulate the expression of N-acetyltransferase 10 (NAT10), an enzyme responsible for N4-acetylcytidine (ac4C) modification of mRNAs. ac4C-modified Myc mRNAs show higher translation efficiency, enabling rapid synthesis of MYC protein and supporting robust T cell expansion. Conditional deletion of Nat10 in mouse T cells causes severe cell cycle arrest and limitation of cell expansion due to MYC deficiency, ultimately exacerbating infection in an acute lymphocytic choriomeningitis virus model. Additionally, T cells from older individuals with lower NAT10 levels show proliferative defects, which may partially account for impaired antiviral responses in older individuals. This study reveals a mechanism governing T cell expansion, signal-dependent mRNA degradation induction and the potential in vivo biological significance of ac4C modification in T cell-mediated immune responses.